Column–beam moment capacity ratio and seismic risk of reinforced concrete frame building. Issue 3 (27th April 2018) - Mistri, Abhijit; Sarkar, Pradip; Davis, Robin
Abstract : The major international design codes recommend a minimum value of the column–beam moment capacity ratio (MCR) to ensure a preferred collapse mechanism in multi-storey buildings. The aim of the work presented in this paper was to understand the basis of the discrete values of the MCR recommended in design codes through a probability-based seismic risk assessment method. The results obtained suggest that MCR criteria need not be imposed for buildings located in low-seismicity zones as other design criteria ensure an acceptable level of safety for buildings in these seismic zones. On the other hand, it was found that even a very high MCR cannot ensure a preferred collapse mechanism for buildings in zones of higher seismicity. The code approach of a single value of the MCR is therefore not adequate for consistent performance in different seismic zones or for performance objectives.